Selfitis and body image satisfaction among undergraduates in a Nigerian private university - Oluwaseyi Isaiah Olabisi; Opeyemi Adebisi; Adeolu Ejidokun; Adeniyi Makinde; Titilope Awotunde; Deborah Esan (Elsevier, 2024)
Background: Selfitis and body image satisfaction among youths are major concerns for mental health practitioners globally. This study determined the level of selfitis and body image satisfaction among undergraduates' students in a Nigerian private university, as well as the relationship between the two concepts. Method: A descriptive research design was employed to recruit 440 undergraduate students from Bowen University, Iwo in Nigeria, using a proportionate sampling technique. Selfitis Behaviour scale and body self-image questionnaire-short form were used to collect the data. The data were analysed using statistical packages for social sciences (SPSS) Version 21. Both descriptive and inferential statistics were carried out at p < 0.05. Results: The mean age of the respondents was 20.9 ± 2.4, and the majority (69.5 %) of the undergraduate students were females. More than half (58.2 %) of students had borderline selfitis and 34.5 % had chronic selfitis. Environmental enhancement (3.25 ± 0.9) and attention seeking (3.15 ± 1.0) were the main reasons students were involved in selfitis. Most (60.9 %) of the students were partially satisfied with their body image, and only few (17.7 %) were highly satisfied. Negative affect (4.30 ± 1.1), fatness evaluation (4.22 ± 1.2) and overall appearance (4.04 ± 1.0) were the most common body image satisfaction subscales identified. There was a negative correlation between body image satisfaction and selfitis behaviour among the undergraduate students (r = -0.334**, p-value < 0.0001). Conclusion: More than half of the undergraduates had borderline selfitis and one third were suffering from chronic selfitis. Many students were satisfied with their body images, and body image satisfaction negatively influenced selfitis behaviour. Therefore, more awareness should be created on positive self-image and acceptance of oneself among undergraduates.